2020
DOI: 10.1177/0898756420968306
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Orodental Disorders in South Brazilian Cart Horses: Walking a Tightrope Between Animal Welfare and Socioeconomic Inevitability

Abstract: In developing and emerging countries, many people make a living from picking municipal solid waste to sell for reuse or recycling. These people depend on cost-effective transport vehicles like horse-drawn carts. It is indisputable that the general health of these horses not only plays a major economic role but is a welfare issue as well. Orodental disorders are likely to be of particular importance as they directly impair health, performance, and therefore influence animal welfare and income. However, studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…This combination of findings supports the conceptual premise that mechanical stimuli, likely differing by tooth position, may be of great etiological importance in the EOTRH syndrome complex. Interestingly, Kunz et al (48) reported that they have found no signs of EOTRH in 70 Brazilian working horses, aged 18 ± 4 years, which have never had any dental treatment. How dental treatment, tooth curvature, and direction and rate of tooth eruption affect IIA changes remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This combination of findings supports the conceptual premise that mechanical stimuli, likely differing by tooth position, may be of great etiological importance in the EOTRH syndrome complex. Interestingly, Kunz et al (48) reported that they have found no signs of EOTRH in 70 Brazilian working horses, aged 18 ± 4 years, which have never had any dental treatment. How dental treatment, tooth curvature, and direction and rate of tooth eruption affect IIA changes remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…(2009) identified 90 % of investigated infundibula showing at least mild infundibular lesions, but in only 65 % visible changes on the occlusal surface occurred [ 51 ]. In a study examining mainly middle-aged working horses, we previously observed a 32.9 % prevalence of cheek tooth occlusal infundibular caries lesions [ 52 ]. Similarly, in the presented case, carious occlusal changes of the tooth 209 were less severe compared to the extensive subocclusal process.…”
Section: Discussionmentioning
confidence: 99%
“…Among the diseases reported by owners in eligible publications covering multiple diseases, dental disorders may have severe economic consequences due to their secondary effects such as weight loss and colic [99,103]. Since dental disorders are preventable diseases, evidence of their socioeconomic impact could facilitate investments in the education of owners and veterinary personnel and in the distribution of dental equipment to veterinary facilities [104].…”
Section: Other Diseasesmentioning
confidence: 99%